Oral health knowledge, practice and dental plaque maturity status of hearing-impaired children - Haliza Tugeman; Normastura Abd Rahman; Azizah Yusoff; Mohd Khairi Md Daud (Penerbit Universiti Kebangsaan Malaysia, 2016)
Hearing impairment is an unseen handicapped that lead to communication barriers which might impede knowledge transfer. The aim of this study was to compare the oral health knowledge, practice and dental plaque maturity between hearing-impaired (HI) and normal children. A cross sectional study was conducted among children aged 7-14 years old. The HI children were recruited from a special school for the deaf while the normal children were from the primary and secondary schools in Bachok, Kelantan. The oral health knowledge and practice was assessed by face to face interview whilst the dental plaque maturity status was evaluated using GC Tri Plaque ID Gel™ (TPID). The data was analysed using IBM SPSS version 22. HI children had poor oral health knowledge and oral health practice compared to normal children (p<0.05). HI children had significantly more matured plaque compared to normal children with mean (SD) DPMS of 1.8 (0.57) and 1.3 (0.20), respectively (p<0.001). In conclusion, there were poor oral health knowledge, poor oral hygiene practice and high plaque maturity among HI children.